Effect of Occupational Exposure to Crystalline Silica on Pulmonary Indices in Tile and Ceramic Workers - Nourmohammadi, Mohammad; Yari, Saeed; Rahimimoghadam, Somayeh (Asian Pacific Journal of Environment and Cancer, 2022)
Objective: The ceramic industry has developed rapidly in recent decades and the exposure of workers in this industry to dust containing crystalline silica has also increased. the aim of this study was the evaluation of worker’s exposure to crystalline silica and its impact on pulmonary indices in a tile and ceramic industry. Method: In this descriptive and analytical study, 60 repairable samples from six sections of tile and ceramic workers were collected and analyzed by NIOSH 7601 sampling method. Pulmonary parameters were measured using a spirometer. The tests were performed according to the criteria of ATS 2005 Finally data analysis was performed. Result: The mean age in the exposed group to dust and control group was 38.91 ± 5.96 years and work experience was 6.58 ± 1.74 years. 25% of them was smokers and 30% of the workers used respiratory protection devices. The highest average exposure rate to silica were in the stone crusher section (0.43 mg/m3) the lowest average exposure rate to silica dust was in the packing section. Discussion: the result show 95 percent of samples were higher than the NIOSH occupational exposure limit FVC and FEV1 in the groups exposed to silica dust decreased significantly, which could be due to the presence of dust in the working environment.